(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2023)
The transition from a high school student to a college student is an important period in determining eating behavior choices that contribute to the quality of life. The research objective was to analyze the types of eating behavior and their relation to the nutritional status of students. The research design was a crosssectional study involving 230 subjects. Eating behavior data was obtained based on filling out the Dutch Eating Behavior Questionnaire (DEBQ), weight and height data were obtained by direct measurement. The results showed that the average scores for emotional eating, external eating, and restricted eating were 2.27±0.74;3.30±0.56, and 2.41±0.75. A total of 15.7% of the subjects were overweight and obese and 7,8% subjects were undernourished. External eating behavior (p=0.008, r=-0.175) and restraint eating (p=0.000, r=0.485) were significantly related to BMI. Restrained eating scores were higher in subjects with overweight and obese status, while external eating scores were higher in subjects with normal and less nutritional status. The results of this study can be an input for developing a preventive strategy for nutritional problems in students with an eating behavior approach.